The Bethesda System for Reporting Thyroid Cytopathology: A Cytohistological Study. (16th April 2020) - Anand, Bakiarathana; Ramdas, Anita; Ambroise, Marie Moses; Kumar, Nirmal P.
Abstract : Introduction . The Bethesda System for Reporting Thyroid Cytopathology (TBSRTC) is a significant step to standardize the reporting of thyroid fine needle aspiration (FNA). It has high predictive value, reproducibility, and improved clinical significance. Aim . The study was aimed to evaluate the diagnostic utility and reproducibility of "TBSRTC" at our institute. Methods and Material . The study included 646 thyroid FNAs which were reviewed by three pathologists and classified according to TBSRTC. Cytohistological correlation was done for 100 cases with surgical follow-up and the sensitivity, specificity, positive predictive value, negative predictive value, diagnostic accuracy, and risk of malignancy (ROM) were calculated. The interobserver variation among three pathologists was also assessed. Results . The distribution of cases in various TBSRTC categories is as follows: I—nondiagnostic 13.8%, II—benign 75.9%, III—atypia of undetermined significance (AUS)/follicular lesion of undetermined significance (FLUS) 1.2%, IV—follicular neoplasm (FN)/suspicious for follicular neoplasm (SFN) 3.7%, V—suspicious for malignancy (SM) 2.6%, and VI—malignant 2.8%. The sensitivity, specificity, positive predictive value, negative predictive value, and diagnostic accuracy are 72.4%, 94.3%, 84%, 89.2%, and 87.9%, respectively. The ROM of various TBSRTC categories were II—8.5%; III—66.7%; IV—63.6%; and V and VI—100%. Cohen's Weighted Kappa score was 0.99 which indicates almost perfect agreement among the three pathologists. Conclusions . Our study substantiates greater reproducibility among pathologists using TBSRTC to arrive at a precise diagnosis with an added advantage of predicting the risk of malignancy which enables the clinician to plan for follow-up or surgery and also the extent of surgery.